Modelling of the partial discharge within insulation paper under double spherical cavity - Roslan, Muhammad Hakirin; Azis, Norhafiz; Kadir, Mohd Zainal Abidin Ab; Jasni, Jasronita; Yousof, Mohd Fairouz Mohd (Elsevier, 2026)
This paper describes analyses on the simplified Partial Discharge (PD) model based on the Finite Element Method (FEM) approach. The resultant model was used to evaluate the impact of double spherical cavities on the PD activities within insulation paper. The PDs were simulated based on the 3D model of insulation paper that consisted of conductor, mineral oil and insulation paper. Two spherical cavities namely spherical cavity 1 (C1) and spherical cavity 2 (C2) were introduced in the insulation paper, with C1 located at the center (L1) and C2 at the left corner (L2). Four diameter size combinations of C1 and C2 were considered with 0.5 mm and 0.8 mm respectively. Based on the Phase-Resolved Partial Discharge (PRPD) patterns obtained, the PD activities in C1 and C2 can be clearly distinguished. The spherical cavity at L1 is found to contributes to the higher total charge and PD occurrence per cycle than at L2. The spherical cavity of 0.5 mm contributes to the higher PD occurrence per cycle as compared to 0.8 mm. However, the spherical cavity of 0.8 mm contributes to the higher total charge per cycle as compared to 0.5 mm.